Presentation of a Wavelet‑Based Harmonic Model for Tidal Level Forecasting at Sabah and Sarawak - Abubakar, Auwal Garba; Mahmud, Mohd Razali; Tang, Kelvin Kang Wee; Husaaini, Alhaji (Geomatics and Environmental Engineering, 2020)
The world´s tides are a result of the combined forces of celestial forces and centrifugal force exerted by the Earth‑Moon and the Sun acting on the water body, earth tides and the atmospheric tides. Harmonic analysis is the most popular and widely accepted method used for the processing and expression of tidal behavior as well as its characteristics. Despite its strengths, harmonic analysis has a few drawbacks when short data are involved for long term‑prediction. However, to enhance the accuracy of the popular methodology of harmonic analysis (HA), this study presents a wavelet‑based harmonic model for tidal analysis and prediction. Six months of water level heights at four tide gauge stations in Sabah and Sarawak of Malaysia were employed. The results obtained agrees with the original data when a comparison was made. The root mean square error (RMSE) and Pearson correlation coefficient (r) are the statistical index tools applied to test the functioning of the model. The residual error is the deviation between the original data and the predicted data which was also computed in this study. The new wavelet‑based harmonic model improves the accuracy of prediction. Moreover, the model is efficient and feasible for tidal analysis and prediction.